Evaluation of inflammatory biomarkers and their association with anti-SARS-CoV-2 antibody titers in healthcare workers vaccinated with BNT162B2 - Leno-Duran, Ester; Serrano-Conde, Esther; Salas-Rodríguez, Ana; Salcedo-Bellido, Inmaculada; Barrios-Rodríguez, Rocío; Fuentes, Ana; Viñuela, Laura; García, Federico; Requena, Pilar (Frontiers in Immunology, 2024)
Introduction: Vaccine-induced immunity against COVID-19 generates antibody and lymphocyte responses. However, variability in antibody titers has been observed after vaccination, and the determinants of a better response should be studied. The main objective of this investigation was to analyze the inflammatory biomarker response induced in healthcare workers vaccinated with BNT162b2, and its association with anti-Spike (a SARS-CoV-2 antigen) antibodies measured throughout a 1-year follow-up.Methods: Anti-spike antibodies and 92 biomarkers were analyzed in serum, along with sociodemographic and clinical variables collected by interview or exploration.Results: In our study, four biomarkers (ADA, IL-17C, CCL25 and CD8α) increased their expression after the first vaccine dose; and 8 others (uPA, IL-18R1, EN-RAGE, CASP-8, MCP-2, TNFβ, CD5 and CXCL10) decreased their expression. Age, body mass index (BMI), smoking, alcohol consumption, and prevalent diseases were associated with some of these biomarkers. Furthermore, higher baseline levels of T-cell surface glycoprotein CD6 and hepatocyte growth factor (HGF) were associated with lower mean antibody titers at followup, while levels of monocyte chemotactic protein 2 (MCP-2) had a positive association with antibody levels. Age and BMI were positively related to baseline levels of MCP-2 (=0.02, 95%CI 0.00-0.04, p=0.036) and HGF ( =0.03, 95%CI 0.00-0.06, p=0.039), respectively. Conclusion: Our findings indicate that primary BNT162b2 vaccination had a positive effect on the levels of several biomarkers related to T cell function, and a negative one on some others related to cancer or inflammatory processes. In addition, a higher level of MCP-2 and lower levels of HGF and CD6 were found to be associated with higher anti-Spike antibody titer following vaccination.